Bariatric surgery, osteoarthritis and arthroplasty of the hip and knee in Swedish Obese Subjects – up to 31 years follow-up of a controlled intervention study. Issue 5 (May 2023) - Lohmander, L.S.; Peltonen, M.; Andersson-Assarsson, J.C.; Maglio, C.; Sjöholm, K.; Taube, M.; Jacobson, P.; Svensson, P-A.; Carlsson, L.M.S.; Ahlin, S.
Summary: Objective: To study the long-term effect of obesity and bariatric surgery on incidences of osteoarthritis and arthroplasty of hip and knee. Design: Hazard ratios (HR) and incidence rates (IR) of osteoarthritis and arthroplasty of hip and knee were studied in the prospective, controlled, non-randomized Swedish Obese Subjects (SOS) study (bariatric surgery group, n = 2007; matched controls given usual obesity care, n = 2040) and the SOS reference cohort ( n = 1135, general population). Osteoarthritis diagnosis and arthroplasty for osteoarthritis were captured from the National Swedish Patient Register. Median follow-up time was 21.2 (IQR 16.4–24.8), 22.9 (IQR 19.1–25.7), and 20.1 years (IQR 18.7–20.9) for the control group, surgery group and reference cohort, respectively. Results: The surgery group displayed lower incidence of hip osteoarthritis (IR 5.3, 95% CI 4.7–6.1) compared to controls (IR 6.6, 95% CI 5.9–7.5, adjHR 0.83, 95% CI 0.69–1.00) but similar incidence of hip arthroplasty. Similar incidence of knee osteoarthritis was observed in the surgery group and controls, but knee arthroplasty was more common in the surgery group (IR 7.4, 95% CI 6.6–8.2 and 5.6, 95% CI 4.9–6.4, adjHR 1.45, 95% CI 1.22–1.74). The reference cohort displayed lower incidences of osteoarthritis and arthroplasty of hip and knee compared with the surgery group and controls. Conclusion: Bariatric surgery did not normalize the increased risk of knee and hip osteoarthritis in patients with obesity but was associated with an increased incidence of knee arthroplasty compared to the control group. With the limitations inherent to the present data, additional studies are needed to confirm these results. Trial registration: clinicaltrials.gov Identifier: NCT01479452 .